2016
DOI: 10.1371/journal.pone.0156371
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond-Laser-Pulse Characterization and Optimization for CARS Microscopy

Abstract: We present a simple method and its experimental implementation to determine the pulse durations and linear chirps of the pump-and-probe pulse and the Stokes pulse in a coherent anti-Stokes Raman scattering microscope at sample level without additional autocorrelators. Our approach exploits the delay line, ubiquitous in such microscopes, to perform a convolution of the pump-and-probe and Stokes pulses as a function of their relative delay and it is based on the detection of the photons emitted from an appropria… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“… 58 To ensure optimal spectral focusing, the excitation beams have to be equally stretched based on their initial transform limited pulse durations. Therefore pump and Stokes beams travelled through 450 mm and 650 mm of glass respectively, which stretched the pulses to ≈6.9 ps and 2.8 ps ( ref. 59 ) providing a spectral resolution of ≈15 cm –1 to best match the Raman line widths of the CH wavenumber region.…”
Section: Methodsmentioning
confidence: 99%
“… 58 To ensure optimal spectral focusing, the excitation beams have to be equally stretched based on their initial transform limited pulse durations. Therefore pump and Stokes beams travelled through 450 mm and 650 mm of glass respectively, which stretched the pulses to ≈6.9 ps and 2.8 ps ( ref. 59 ) providing a spectral resolution of ≈15 cm –1 to best match the Raman line widths of the CH wavenumber region.…”
Section: Methodsmentioning
confidence: 99%
“…The latter and the remainder of the pump beam are attenuated, expanded by telescopic beam expanders, individually chirped by SF6 optical-glass blocks and temporally overlapped by a delay line. It was shown that manipulation of the beam chirping values can lead to improvements in CARS imaging performance, such as an increase in CARS signal intensity [21] or, by exploiting the spectral focusing principle [22], an increase in spectral resolution and therefore in image signal-to-background ratio [23][24][25]. We pursued the latter approach: spectral focusing was achieved thanks to the optical-glass blocks by inducing a similar amount of chirping at the sample plane for the two beams [22].…”
Section: Protocolmentioning
confidence: 99%
“…We pursued the latter approach: spectral focusing was achieved thanks to the optical-glass blocks by inducing a similar amount of chirping at the sample plane for the two beams [22]. As a consequence, the pulse duration is increased from ~160 fs (~115 fs) at the laser output of the pump (Stokes) beam to ~545 fs (~810 fs) on the sample [25]. Before each experimental session, the delay line position was carefully tuned, analysing the sample-emitted light with a spectrometer (iHR550, with Synapse sCCD camera, Horiba), in order to optimize the temporal overlap and the spectral selectivity for the Raman band of the CH2 bonds.…”
Section: Protocolmentioning
confidence: 99%
“…The system described here provides several advantages over other CARS systems. First, the system makes exciting nonlinear CARS processes more accessible because pulse energies from OPAs used in our configuration are orders of magnitude higher 14 than optical parametric oscillator-based, 2,3,8,20 locked picosecond laser pairs, 7,12 or super-continuum generation systems 1 typically used for CARS imaging. The OPAs used in this work produced >100 nJ per pulse compared to <10 nJ typical of non-OPA systems.…”
Section: Discussionmentioning
confidence: 99%
“…The difference in dependency between FWM and SFG allows the pulse widths of ω p and ω s to be determined by measuring the pulse widths of the FWM and SFG signals. 20 Using this method, the pulse width of ω p was measured as 6.9 ps, while the pulse width of ω s was measured as 2.7 ps. The FWHM spectral bandwidths of the pulses were measured as 16.9 nm for ω p and 11.5 nm for ω s .…”
Section: Pulse Chirp and Spectral Measurementsmentioning
confidence: 99%